Production Relocation of Multinational Companies from China and Chances for Vietnam - Mai, Nguyen Thi Thanh; Phuong, Pham Thi (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 36 No 5E, 2020)
Since the intense US-China trade war and the global outbreak of the Covid-19 pandemic, multinational companies’ tendency to diversify production activities and disperse their foreign direct investment (FDI) out of China became more visible. In this context, Vietnam has the opportunity to become a new global manufacturing hub. It remains to be seen whether Vietnam can attract that FDI inflow from multinational companies (MNCs) or not, especially in the context of unpredictable competition between many potential countries such as India, ASEAN countries and China who actively finds ways to retain foreign investors. The objectives of this article are to analyze the trend of relocating production sites of MNCs from China, and its causes, and factors attracting a production relocation wave in Vietnam, thereby giving some implications to increase the difference of Vietnam in this race to attract investment from foreign manufacturers.